Microscopic Characteristics of Kinking Phenomenon in Vertically Free-Standing Nanowires - Zhina Razaghi; Guo-zhen Zhu (Crystals, 2023)
Vertically free-standing nanowires, synthesized through vapor-based growth, can undergo changes in their growth directions known as kinking. These alterations can significantly influence the physical and chemical properties of nanowires, thereby expanding their potential applications. The occurrence of kinks is commonly associated with variations in vapor, temperature, seed, and/or their combinations. However, the interplay among different growth factors complicates the identification of the dominating factor and, consequently, limits precise control over nanowire morphology. Theoretical models, incorporating factors like supersaturation, wetting angle, nanowire size, and surface/interface energies tied to growth conditions, have been developed to describe and predict kinking during nanowire growth. While a few pivotal parameters, such as surface/interface energies and wetting angles, can be subtly adjusted through minor alterations in growth conditions, accurately predicting the occurrence of kinks remains a practical challenge. Conversely, in the present review, we attempted to elucidate connections between microscopic aspects, such as changes in composition and the formation of defects, and the nucleation and progression of kinks. This effort aims to construct a predictive framework that enhances our understanding of the tendencies in nanowire growth.